Clostridium butyricum ameliorates indomethacin-induced enteropathy by promoting MUC2 secretion via suppressing the Notch pathway - Zhu, Lanping; Luo, Yang; Liu, Yaxin; Sun, Siyuan; Yuan, Junjie; Zhang, Lijun; Zhong, Weilong; Ma, Shuang; Yu, Zihan; Zhou, Jinjie; Chen, Xin; Zhao, Jingwen (Frontiers in Microbiology, 2025)
Nonsteroidal anti-inflammatory drug (NSAID) enteropathy is a serious clinical complication with no effective treatments available. Modulating the intestinal microbiota through dietary and nutritional targets is a promising strategy for preventing NSAID enteropathy. This study aimed to investigate the protective effect and underlying mechanisms of the probiotic Clostridium butyricum (CB) on indomethacin (IND)-induced enteropathy. C57BL/6J mice received CB treatment for 14 days along with concurrent IND gavage for the final 7 days. Caco2 cells were stimulated with IND to evaluate the effect of CB supernatant (CBS) on the intestinal barrier function, and LS174T cells were used to validate the modulatory action of CBS on the Notch signaling pathway. Our findings revealed that CB treatment prevented anorexia and weight loss, reduced the severity of enteropathy, and decreased the inflammatory response of the small intestine. CB also increased the expression of tight junction proteins and reduced permeability in mice and Caco2 cells. Additionally, CB suppressed apoptosis and promoted proliferation in the small intestine. Further research found that CB increased the number of goblet cells and MUC2 secretion. Mechanistically, CB may promote MUC2 secretion by suppressing the Notch signaling pathway, consistent with the results of intervention in LS174T cells with CBS. In conclusion, CB might prevent NSAID enteropathy by increasing MUC2 secretion through the inhibition of the Notch pathway. Our study identified the potential efficacy of CB as a preventive strategy against NSAID enteropathy and showed promising prospects for CB as a food supplement.